INSURANCE COMPANIES, THEIR IMPORTANCE AND THE RISKS THEY FACE - Bachiri Hamza (International Journal of Innovative Technologies in Social Science, 2024)
Insurance companies occupy an important position within the financial sector of any economy, as they are authorized entities to provide coverage against risks for individuals and institutions, as well as financial intermediaries that accept funds in the form of premiums to be reinvested in various forms of investment. Therefore, in this chapter, we will discuss the nature of insurance companies, their types, and their importance in national economies, in addition to addressing their various tasks and functions, the different forms of their administrative organization, as well as presenting the types of risks they face in their activities according to various classifications.